Memorija in/ali spomin? - Jurić-Pahor, Marija (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The discourse of memory and recollection has been on the rise in the last two decades. It has also developed into priority place of interdisciplinary research, a crossing of many different issues and interest spheres: culture, natural science and information technology.It is becoming increasingly clear that memory and recollection are a phenomenon no scientific discipline can claim to be its own only. Moreover, these categories are not synonimous, which means they must not be equalled. The author deals with the distinction between memory and recollection on the basis of current psychological and psychoanalytic conceptualizations, strongly defined by cognitive sciences and neurosciences, relating to social constructionism. She also deals with "socialframeworks of memory", insufficiently considered in these conceptualizations due to the focus on man as individual. Especially important in this context are the theories of the French sociogist Maurice Halbwachs together with the related concepts of communicative and cultural memory (esp. Aleida and Jan Assmann). The author treats them with special regard to to the term generation and transgenerational transmission of trauma suffered by the concentration camps survivors.
Keywords: memorija; memory; spomin; kulturni spomin; kolektivni spomin